(3JTQjM GdYjf hCTcGdgG heOGhGI EYdGdgGs - (3Ydj Hf EHQGgje Hf HNJjThY GdeJWHH,J (B460 (3g` s ((3YHO GdQMef Hf jhfS GdCfUGQi s)
(3ChdgG (B:s
(3bGd Ydi Hf EHQGgje (B: (3QCjJ cd eDda cJGH heUfa BOGH dg SHH MKg Ydjg SjeG Yde GdWH dTQa ehVhYg hLdGdJg aHOCJ ef GdQCS HCTQa GdMhGS hgj GdYjf hEYdGdgG hJTQjMgG hCTcGdgG s
(3BNQgG (B:s
(3hUM di Pdc HGdJLQHI ai SfI SJjf hCQHY eGFI ai GeQCI cHjQI GdSf hai QLd HQFG HYO JfbjI GdLSO HSbhW GdcfOS ef VYa GdHUQ GdPi HdZ HgeG CdG jHUQG eG HYO , hdG jMbbG eG bQH , ef GdYTi HEPG Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B76 - (3U(B125s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B53s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs